2019
DOI: 10.32604/sdhm.2019.04640
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Property of String Beam of Pre-Stressed Glulam Based on Influence of Regulation and Control

Abstract: Applying pre-stress in glulam beam can reduce its deformation and make full use of the compressive strength of wood. However, when the glulam with low strength and the pre-stressed steel with high strength form combined members, materials of high strength can't be fully utilized. Therefore, this study puts forward the idea of regulating and controlling string beam of pre-stressed glulam. By regulating and controlling the pre-stress, a part of the load borne by the wood is allocated to the pre-stressed tendon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However, the design service life of the general structure was 50 years in the building structure. Combined with the previous research experience [34], the existing test data was applied to establish creep model for fitting and estimating the long-term deformation of 50 years in this paper.…”
Section: Establishment Of Creep Modelmentioning
confidence: 99%
“…However, the design service life of the general structure was 50 years in the building structure. Combined with the previous research experience [34], the existing test data was applied to establish creep model for fitting and estimating the long-term deformation of 50 years in this paper.…”
Section: Establishment Of Creep Modelmentioning
confidence: 99%
“…Because of no similar research on other forms of prestressed continuous beams, there is no direct comparison. Nevertheless, based on former research [28,29,35], compared with Glulam beams, the bearing capacity of the continuous prestressed beams can be increased by 106.4% to 652.4%, and the bearing capacity of other types of prestressed Glulam beams was increased by 28.5% to 28.8% [21,26]. erefore, compared with other types of prestressed beams, the prestressed continuous beam proposed is more effective and feasible.…”
Section: Contrastive Analysis Of Continuous Beams and Simply Supported Beamsmentioning
confidence: 99%
“…e results indicated that bending capacity and deformation capacity could be improved significantly. e use of prestress for structural strengthening of timber structures was detailedly assessed, and then prestress was used to strengthen the mechanical properties of the Glulam beams [20][21][22][23][24][25][26][27][28][29]. Wei et al [21] proposed a novel steel-reinforced PBSL beam in which steel bars or prestressed steel bars were embedded in bamboo-composite beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To take full advantage of material properties and enrich structural forms, the author of this paper based on the previously proposed prestressed glulam simply supported beams, and then exploited the prestressed glulam continuous beam through a new set of connection apparatuses, as shown in Fig. 1a [20,21]. The continuous beam combined two glulam beams through the new connection apparatus.…”
Section: Introductionmentioning
confidence: 99%